Omissão do garantidor em face de conduta delitiva de terceiro: concurso, autoria colateral ou fato penalmente irrelevante? - Neves, Cícero Robson Coimbra (2008)
This paper aims to examine to what extent a security guarantor or surety should be deemed responsible in the event that the primary obligor or principal fails to meet an obligation to which he/she is bound and thus enters default or delinquency. On the grounds of general legal theory and principles, this should be understood as a case of concerted action whereby the guarantor s liability arises from complicity and participation, and thus engages in the so-called participation by omission (i.e. failure or breach of a duty to act). While on one hand it is found to be applicable as a normative convention by Brazilian law, on the other hand such understanding appears to be incompatible with basic principles of culpability. More careful study is required in order to find out whether a guarantor s omission should be interpreted under the principles of criminal law and, if such is the case, whether this should be understood as concerted action or participation. This paper further aims to focus on real cases pursuant to two currently applicable criminal codes relying on different procedural guidelines, namely Ordinary Criminal Law and Military Criminal Law. The introduction chapter outlines the premises in this paper and describes the criminal offence theory ranging from a system referred to as causal (i.e. classical) up to currently functional systems, of normative nature, particularly those as understood by Günther Jakobs and Claus Roxin. Given the several systems implied, this research required a guiding principle that could, among other things, help to understand criminal science dogmas in military criminal law. The system devised by Hans Welzel, i.e. finalism, was then regarded as the most suitable guiding principle. Since there is a long way still to go, this research aims not only to resolve some doubts, but also to point out that some of the issues that are currently covered by legal theory and principles should be reconsidered with a view to searching for more appropriate and fairer solutions on the grounds of the nullum crimen sine culpa principle